Psychiatric safety associated with hormone replacement therapy for menopausal symptoms: a real-world study of the FDA adverse event reporting system - Chen, Nan; Li, Lei; Fu, Chun-li; Ren, Yi (Frontiers in Psychiatry, 2025)
BackgroundMenopause is a significant phase in a woman’s life and is characterized by the cessation of ovarian function and a decline in endogenous ovarian hormone levels. This hormonal transition is often accompanied by debilitating symptoms, such as hot flushes, which can significantly impair quality of life. Hormone replacement therapy (HRT) is commonly used to alleviate these symptoms; however, there are concerns regarding its safety, particularly its impact on psychiatric health, in real-world settings. This study aimed to systemically investigate the psychiatric risks associated with HRT in menopausal women using real-world data.MethodsWe conducted disproportionality analyses by using data from the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) collected from January 1, 2004, to September 30, 2024, to calculate the reporting odds ratio (ROR) for psychiatric adverse events (pAEs) across four FDA-approved HRT categories. Risk factors for pAEs were further explored by multivariate logistic regression analysis.ResultsAmong 43,340 HRT-related adverse event reports, 2,840 (6.6%) involved pAEs, with a median patient age of 59 years (IQR: 52–67). A total of 43 pAEs at the preferred term level were identified associated with HRT. After adjustment for confounders, HRT related pAEs revealed an increased risk in females younger than 40 years old. Furthermore, those taking HRT by systemic route had higher risk of pAEs than local administration. Additionally, for different HRT type, only estrogen alone or estrogen combined progestogen had increased risk for HRT-related pAEs. Specifically, estrogen monotherapy was associated with an increased risk of mood disorder (OR=1.83, 95%CI: 1.42–2.37) and sleep disturbances (OR=1.57, 95%CI: 1.26–1.98)- related pAEs, while a reduced risk of suicidal and self-injurious behavior (OR=0.33, 95%CI: 0.18−0.61)-related pAEs comparing with combination therapy with progestogen. Notably, only combination therapy increased the risk of pAEs related to depressed mood and disturbances.ConclusionIt is necessary to conduct personalized risk stratification in HRT management, prioritizing age, administration route, and regimen type. While, further clinical investigations are needed to validate these findings and refine HRT safety strategies.